Método computacional para el cálculo de la eficiencia de perforación de pozos petrolíferos mediante el método de los elementos finitos (2015)
In this paper the relationship between MSEs and MSEf calculated via Finite Element Method are presented. For these purpose we have used a CAD model of PDC bit and a homogeneus, lineal and isotropic model for rock properties. Data of vibrations phenomenon were considered.